PENDIDIKAN ANTIKORUPSI DALAM MEMBENTUK KARAKTER MAHASISWA: STUDI LITERATUR DAN IMPLIKASI TERHADAP KESADARAN HUKUM - Agus Setiawan (Educatus, 2023)
The prevalence of corruption remains a significant challenge, as evidenced by the increasing number of cases reported and circulated through various social media platforms. This trend poses serious threats to a nation’s economy, its foundational values, and the integrity of its ideological framework. Therefore, preventive and educational measures are essential to combat and eradicate corruption effectively. This paper explores anti-corruption education as a strategic effort to develop students’ character, focusing on the cultivation of free will, moral awareness, and responsible individual behavior through the maximization of student potential. The study adopts a qualitative research methodology, primarily utilizing literature review techniques. The analysis is based on a variety of scholarly sources, including books, academic journals, and other credible media. The findings underscore the necessity of integrating anti-corruption education into higher education curricula. This includes the development of humanistic character traits, comprehensive knowledge of corruption and its legal implications, familiarity with existing legal frameworks, and the promotion of law-abiding behavior. Furthermore, fostering legal awareness and civic responsibility among university students is vital in nurturing a generation that is conscientious, ethically grounded, and committed to national integrity and public accountability.